Coherence and Cohesion: An Analysis of The Students’ Recount Paragraphs - Maheswari, Komang Citra Paramita (Jurnal Penelitian Mahasiswa Indonesia, 2024)
The research aimed to analyze the aspects of coherence and cohesion found in paragraphs written by eighth-grade students at SMP Negeri 1 Sukasada. To achieve this goal, the researcher used a parallel convergent mixed-method design, which allowed the inclusion of qualitative and quantitative data. The data collection process involved the use of cluster random sampling where several classes were randomly selected from the population of classes available at the school. Subsequently, from the selected classes, class 8A was chosen as one of the sample classes for this research. The data obtained consisted of students’ written documents, which were then analyzed using both qualitative and quantitative approaches. The results of the analysis showed that the students were able to demonstrate good coherence in their descriptive paragraph writing. Therefore, these findings underscored the importance of the teacher’s role in guiding students on the significance of coherence and cohesion in writing. By providing a deeper understanding of these concepts, it was hoped that students would become more aware of how crucial these two aspects were in composing effective and well-structured texts. Thus, it was expected that ongoing teaching efforts on coherence and cohesion would improve the overall quality of students’ writing.